3x-4x+5x-9x=

Simple and best practice solution for 3x-4x+5x-9x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-4x+5x-9x= equation:


Simplifying
3x + -4x + 5x + -9x = 0

Combine like terms: 3x + -4x = -1x
-1x + 5x + -9x = 0

Combine like terms: -1x + 5x = 4x
4x + -9x = 0

Combine like terms: 4x + -9x = -5x
-5x = 0

Solving
-5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-5'.
x = 0

Simplifying
x = 0

See similar equations:

| f(x)=x^2-16x+67 | | r+r+8=6 | | =(65000)x(1+0.016)100 | | 6a-1=17 | | (y-3)(y-3)=2y^2+2y-12 | | s(t)=-16t^2+20t+6 | | H(x)=25-y | | 2x-5x+5=10 | | t=240t-16t^2 | | 115+59+135+51=x | | 2x+48=12x+8 | | 2=s-2 | | 55+.25x=45+.35 | | 26x^2-2x=0 | | 12x-18=8x+6 | | 890=5(x+16) | | 3-20x^2=11x | | 10x^2+25x+3=0 | | 2=-1t | | .14x+2520=2400 | | 7q+5q= | | 6x^4-10x^3-6x^2= | | x-3.4=-12 | | 6x-26=5x | | 4/5x=7 | | y^2+9=2y^2+2y-12 | | -19x^2-12x^2+16x=0 | | 8x-52=4 | | -8(n-6)=5-7n | | -t/4=-3π | | x-10.4=4.6 | | 4y=4x+24 |

Equations solver categories